KUAT GESER KOMPOSIT BAJA – BETON DENGAN VARIASI BENTUK PENGHUBUNG GESER DITINJAU DARI UJI GESER MURNI - Lahamukang, Krisantus M.; Pah, Jusuf J. S.; Messah, Yunita A. (Jurnal Teknik Sipil, 2014)
Composite plan assumes that steel and concrete collaborating in bearing the working burden; this will result in a more economical profile design. Besides, the composite structure also has several advantages, such as stronger and more rigid than the non-composite structure. To ensure coherency between the concrete and steel beams, it must be installed a shear connector device on the steel that connected with concrete. The purpose of this study was to determine which shear connector’s strength is stronger; especially the Stud type shear connector with steel quality of 305,17 MPa and the L type shear connector with steel quality of 406,10 MPa. Specimens used were steel-concrete composite with a length of 200 mm, width 164 mm and height of 280 mm with the quality of two types of concrete quality which are 17 MPa and 20 MPa, the composite specimens using two types of shear connector, which are Stud type shear connector and L type shear connector. Concrete mixture planning refers to SK SNI T-15-1990-03. Result of this study shows that stud type shear connector form strongly resists the shear of a steel composite as much as 26,50 KN for concrete quality of 17 MPa and 33,83 KN for concrete quality of 20 MPa.